PENGARUH KINERJA APARATUR KEPOLISIAN BAGIAN SATUAN LALU LINTAS TERHADAP KEPATUHAN BERLALU LINTAS MASYARAKAT DI KECAMATAN BANYUWANGI - Eva Prastiwi, Yurika; Bahri, Subur; Wilujeng, Sri (JURNAL KATARSIS, 2021)
Abstract : The Effect of Performance of the Police Apparatus in the Traffic Unit Section on Cross-Community Compliance in Banyuwangi District. In traffic there are still many Banyuwangi people who do not comply with traffic regulations. Judging from the frequency of Banyuwangi people who violate traffic signs, administrative violations, and other traffic regulations. Among law enforcement officials, traffic police often deal directly with the community, especially road users. This study aims to get a real picture of the performance of the police apparatus, especially the traffic unit section, to improve the compliance of community traffic in Banyuwangi District. However, if seen from the results of performance (X) based on the specified indicators, namely discipline (X1) and apparatus education (X2), the results show that the discipline of the police apparatus in the traffic unit has aninfluence on community traffic compliance, while the police apparatus education has no effect on direct community traffic compliance. For this reason, it is necessary to increase the level of discipline of the apparatus both in terms of guarding and traffic patrol so as to be able to increase public compliance even more in traffic.